2020
DOI: 10.1111/os.12850
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Multiple Doses of Intravenous Tranexamic Acid on Perioperative Blood Loss in Total Knee Arthroplasty: A Randomized Controlled Study

Abstract: Objective To identify the efficacy and safety of multiple doses of intravenous tranexamic acid (IV‐TXA) following primary total knee arthroplasty (TKA) with a tourniquet. Methods This is a single‐blind randomized controlled study that recruited osteoarthritis patients who had undergone primary unilateral TKA from May 2019 to May 2020 at our medical center. A total of 300 patients were randomly divided into three groups to receive: one dose (1 g) of IV‐TXA before skin incision combined with one dose (1.5 g) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…36 Kang et al found that three doses of TXA decreased blood loss and diminished inflammatory and fibrinolytic responses more than a single dose or two doses in elderly patients. 27 Similar results were reported by using a five-dose in hip and knee surgery. 34,35 Goyal et al showed that there was no significant beneficial effect of three doses of TXA in bilateral total knee arthroplasty compared to a single dose.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 78%
See 1 more Smart Citation
“…36 Kang et al found that three doses of TXA decreased blood loss and diminished inflammatory and fibrinolytic responses more than a single dose or two doses in elderly patients. 27 Similar results were reported by using a five-dose in hip and knee surgery. 34,35 Goyal et al showed that there was no significant beneficial effect of three doses of TXA in bilateral total knee arthroplasty compared to a single dose.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 78%
“…This results is not consistent with clinical trial studies in hip and knee arthroplasty and no related literature reported in shoulder arthroplasty. 27,34,35,36,62 There is a consensus among surgeons that less bleeding is better for patients, but it is unclear whether differences in bleeding for shoulder arthroplasty are clinically significant.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…33 In addition, the calculating method (Gross and Nadler formula) is widely used in other studies. 26,34,35 Moreover, the calculating method is the same among the three groups, which is the basis of comparison. Therefore, we think the method to calculate blood loss in our study is suitable.…”
Section: Discussionmentioning
confidence: 99%
“…19,[47][48][49][50] The majority of included studies were RCTs, [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][35][36][37][38][39][40]43,44,[46][47][48][49][50] while five were cohort studies including a control group. 19,34,41,42,45 The participants in most of the articles were undergoing elective surgery (n ¼ 3,563) 19-39,41--47,49,50 of which 13 studies investigated total knee arthroplasty patients which, at least partly, is an inflammatory condition (n ¼ 1,918), 20,22,24,25,27,34,35,[37][38][39]42,...…”
Section: Resultsmentioning
confidence: 99%